Composition and properties tailoring in Mg2+ codoped non-stoichiometric LuAG:Ce, Mg scintillation ceramics. Issue 4 (April 2017) - Liu, Shuping; Mares, Jiri A.; Babin, Vladimir; Hu, Chen; Kou, Huamin; D'Ambrosio, Carmelo; Li, Jiang; Pan, Yubai; Nikl, Martin
Abstract: A comprehensive study of the optical, radioluminescence and scintillation properties of both the Lu 3+ rich and Lu 3+ deficient non-stoichiometric Lu3+x AG:Ce, Mg (Lu3+x Al5 O12 :Ce, Mg, x = −4, −1, +1 and +4 at.%) ceramics are performed, completed further by the microstructure and defects characterization. Small deviation from the stoichiometric composition as well as Mg 2+ codoping plays a crucial role in ceramic transparency, radioluminescence intensity and the timing characteristics of scintillation response. The LuAl antisite defects could be suppressed efficiently by controlling Lu 3+ content below stoichiometry of LuAG host. MgO (Mg 2+ ions) as effective sintering aids, can improve both the optical quality and scintillation performance (light yield, scintillation decay times and the ratio of fast decay components). We generally discuss the composition dependence of defects and properties tailoring. We also performed the systematic comparative study with the stoichiometric LuAG:Ce, Mg ceramic and the commercial BGO and LuAG:Ce single crystals.